Risk Journey Management Strategy for Route Hazard Mapping of Tank Trucks in Fuel Distribution in the Central Java Region - Mustofa, Ikhsan; Raharjo, Susilo Toto; Yusano, Michael; Arifin, Amrul (GoAcademica Research & Publishing, 2024)
PT Pertamina Patra Niaga, a state-owned enterprise in Indonesia, specializes in the downstream oil and gas sector, with a primary focus on fuel distribution across the nation via land and sea. Land transportation, carried out using tank trucks, presents unique challenges due to the high risk of accidents. To address these challenges, PT Pertamina Patra Niaga conducted a Route Hazard Mapping (RHM) and Risk Journey Management (RJM) study. The study identified key factors contributing to tank truck accidents: human error, vehicle condition, and environmental factors. Mitigation strategies include driver training and health assurance to reduce human error, regular maintenance and inspections to ensure vehicle condition, and RHM and RJM to identify and mitigate environmental hazards along routes. Implementing these recommendations is expected to significantly reduce the risk of tank truck accidents and enhance the safety of PT Pertamina Patra Niaga's fuel distribution operations.